Avaliação Dos Processos De Manutenção E Inspeção De Segurança De Barragem Em Usina Hidrelétrica Estudo De Caso - Cruz, Martha de Sousa (Universidade Federal do Tocantins, 2022)
The present work presents, in an exemplified way, the main anomalies observed in a mixed dam and analysis of the state of conservation of civil structures, of the conditions of structural preservation through on-site checks of the maintenance conditions through the performance of visual execution in the dam of the plant. of hydroelectric generation under study, located in the northern region of Brazil, in the State of Tocantins. Based on bibliographic references analyzing scientific publications related to the theme, such as articles, theses, monographs, international materials made available by FEMA (Federal Emergency Management Agency - USA), Law 14.066 / 2020 (amending Law 12.334 / 2010), Normative Resolution No. 696/2015 and the ANA Entrepreneur Manual. Safety inspections are extremely important elements that are part of the Dam Safety Plan, being largely responsible for providing important information regarding the conservation status of the dam, in order to verify the good performance of the dam, inspections should be executed to find possible defects related to the performance considered satisfactory. According to the methodologies studied for perform the inspection routines, aiming to assure the safety conditions of the dams, these must be periodically analyzed, taking into account the inclusion of aging and deterioration of structures or other factors. As a result, maintenance plans for the safety of the dam, regular inspections or special inspections, are vital to the safety of structures in the long term plan and must be executed regularly according to the degree of risk of the structure, in order to mitigate the risks. damage caused by a rupture of the dam and aside to preserve the integrity of the structure, also secure the lives and the environment that can be harmed by its non-compliance.